OC-058 Increased morbidity in overweight and obese liver transplant recipients—a single centre experience with 1325 patients. (28th May 2012) - Hakeem, A; Cockbain, A; Raza, S; Pollard, S; Toogood, G; Attia, M; Ahmad, N; Hidalgo, E; Prasad, K R; Menon, K
Abstract : Introduction: Obesity levels in the UK have risen over the years. Studies from the US and elsewhere have reported variable outcomes in terms of post liver transplant morbidity, mortality and graft survival in obese liver transplant recipients. There are no such reports from the UK. The aim of this study was to analyse the impact of BMI (Body Mass Index) on outcomes following adult liver transplantation. Methods: Data were retrieved from a prospectively maintained institutional database from 1994 to 2009. Patients were stratified into four BMI categories established by the WHO: underweight (<18.5 kg/m 2 ), normal weight (18.5–<25.0 kg/m 2 ), over weight (>25.0–<30.0 kg/m 2 ) and obese (>30.0 kg/m 2 ). Primary outcome was to evaluate post-operative morbidity and secondary measures were overall patient and graft survival. Categorical variables were analysed by χ 2, and continuous variables by one-way ANOVA (p <0.05 was considered significant). Kaplan–Meier curves were used to study the effect of BMI categories on patient and graft survival. Results: 1400 adult transplants were identified. 1325 patients had height and weight measurements and were included in the study. The overall morbidity was higher in overweight (71.9%, p<0.001) and obese patients (69.2%, p<0.001) in comparison to normal weight recipients (64.3%). Post-operative septic events were common in overweight (60.6%, p=0.001) and obese patients (61.0%, p=0.007) in comparison to normal weight patients (50.4%). Post-operative chest infections were much more common in obese (14.2% vs 9.0%, p=0.038) and overweight recipients (17.7% vs 9.0%, p <0.001) in comparison to normal weight recipients. Obese patients had significantly longer intensive care stay than normal weight patients (mean 4.1 vs 3.2 days, p=0.043). The length of post-operative hospital stay was significantly longer in obese (mean 21.5 days, p=0.009) and overweight patients (mean 22.4 days, p=0.000) in comparison to normal weight patients (mean 18.0 days). Similarly, ascitic or drain fluid sepsis was common in overweight patients in comparison to normal weight recipients (16.5 % vs 2.2%, p<0.001). There was no difference in overall graft survival (p=0.222) and patient survival (p=0.196) between the four groups by log-rank test. Conclusion: This is the largest and the only reported UK series on BMI and outcome following liver transplantation. Overweight and obese patients have increased morbidity in terms of septic complications following liver transplantation, with consequent increased length of intensive care and hospital stay. Identifying these patients early and introduction of measures to reduce BMI should be considered to improve outcomes following liver transplantation. Competing interests: None declared.